A case study of the Sandžak day celebration and constructions of the modern Bosniak memory discourse - Czachowska-Aleksić, Nadia (Balcanica Posnaniensia. Acta et studia, 2021)
The paper is a critical analysis of the Sandžak Day celebrations in Serbia. The ritual activities taking place during grand ceremonies as well as the historical narrative presented by the Bosnian elite are subject to reflection in this doubly peripheral area. Using such research categories as ritual, invented tradition, site of memory and historical myth, the elements that constitute the Sandžak-Bosnian identity have been characterized. Their analysis made it possible to define the mechanisms of the construction of the contemporary Bosnian discourse of memory in Sandžak and to identify the visible tendencies of this narrative.